From Datura stramonium L to Hab-o-shefa: manuscript, animal and clinical studies for the treatment of addiction - Abdolali Moosavyzadeh; Razieh Jafari Hajati; Farzaneh Ghaffari; Shabnam Khatami; Niki Vakili Zahir; Mohsen Naseri (Institue of Medicinal Plants, ACECR, 2020)
Background: Due to the lack of drug dependence prevention processes and the low effectiveness of treatment for the withdrawal of addiction and undesirable side effects of synthetic drugs, moving towards the use of reverse pharmacology to produce a less costly, effective, and low-risk drug is inevitable. Objective: Considering the long history of traditional medicine in Iran in the field of diagnosis and treatment of diseases, including addiction, this study was done by looking at the original manuscript of traditional Persian Medicine (PM), animal studies and clinical trial of the effects of Daturra stramonium and Hab-o-shefa for treatment of opiate addiction. Methods: This paper includes three sections: the study of PM textbooks, animal studies and clinical trials based on research conducted. Results: In the study of PM texts, two main pharmacologic ways to treat opioid habits have been described, graduation and replacement. In the research done Daturra's effect on pharmacological withdrawal syndrome in male rats was significantly more than methadone. Hab-o-shefa's toxicology studies did not show any side effects and tissue damage. Animal studies did not show a significant difference in the total score between the methadone group and Hab-o-shefa group. Clinical studies of Hab-o-shefa on the withdrawal syndrome of opioid dependent patients showed the effect of this product on controlling depression and Signs of deprivation compared to placebo and clonidine. The effect of Hab-o-shefa as a preservative in people with opioid abuse reduced craving, anxiety, and depression over time. Conclusion: The results of our studies showed the effectiveness of hab-o-shefa in all phases of addiction treatment. However, further studies are needed to confirm these findings.